Enzymatic studies in normal and repeat breeder buffaloes - DHABALE, R B; SHARMA, N C (The Indian Journal of Animal Reproduction, 2023)
The concentration of various serum enzymes in normal cyclic and repeat breeding buffaloes were studied. The meanlevels ofGPT and GOT were 11 .04±0.96. 49.6±2.60 and 9.87±0.45. 53.22±1 .83 units/Lin normal cyclic and repeat breedingbuffaloes. respectively, the differences were non-significant. Alkaline phosphatase and acid phosphatase levels were significantlyhigher in repeat breeding than normal cyclic buffaloes.
Keywords: Buffaloes; Repeater; AKP; ACP; GOT; GPT